The influence of human, relational, and structural capital on innovative performance in Indonesia's sharia banking industry: The mediating role of dynamic potential and realized absorptive capacity - Satryo, Saptono Budi; Surachman, Surachman; Hussein, Ananda Sabil; Rohman, Fatchur (Asian Economic and Financial Review, 2025)
The challenge for the Sharia Banking industry is product innovation, which is considered unable to meet market needs and lacks high competitiveness compared to conventional bank products. This study aimed to demonstrate the influence of human, relational, and structural capital on innovation performance in the Indonesian Sharia Banking industry. The authors are concerned that dynamic potential absorptive capacity (DPAC) and dynamic realized absorptive capacity (DRAC) can mediate this relationship based on the dynamic capabilities theory. This study obtained 288 valid questionnaires that collected data from several Sharia Bank locations in Indonesia. PLS-SEM is a modeling technique that aims to determine structural equations. The findings of the study indicate that the development of human capital and relational capital, mediated by DPAC and DRAC, enhances innovative performance in Indonesia's Sharia banking sector. Moreover, the mediating role of DRAC, rather than DPAC, showed a significantly greater influence in improving the innovation performance of the antecedent variable, human capital, compared to other antecedent variables, namely relational capital. Theoretically, DRAC acts as a mediator to help banks transform and integrate new knowledge and insights gained from human capital, then transform them into innovative solutions. Banks can enhance their employees' ability to absorb and synthesize various types of knowledge, fostering creativity and innovation that result in stronger and more effective solutions.